Cross-flow Turbine Design with Taguchi Method Approach - Wijaya Pratama, Agung; Arifin, Fatahul; Dewi, Tresna (International Journal of Research in Vocational Studies (IJRVOCAS), 2023)
The current energy demand is very large, while the use of energy, which mostly uses petroleum and coal, is not matched by the availability of energy sources. For this reason, it is necessary to conduct research on alternative energy in order to provide energy security in the future. One alternative energy is water energy, which uses water turbines. This study aims to determine the optimum conditions for design parameters for static pressure and magnitude speed in crossflow water turbine design. The testing was done using finite element method simulation, namely Autodesk CFD. Taguchi methodology analysis is used as an optimization method. The number of blades, blade angle, and water direction angle were set as design parameters with constant water discharge parameters. The resulting static pressure and magnitude velocity were observed as design criteria. The results of the Taguchi method analysis in this study show that the optimum static pressure received from the water turbine is at the number of blades, with 10 blades, a blade angle of 22°, and a water direction angle of 60°. While the optimum velocity of the water turbine is at the number of blades of 6, the blade angle is 20°, and the water direction angle is 60°.